PENGARUH KOMUNIKASI INTERPERSONAL, KOMPETENSI, DAN PENEMPATAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS KEPEMUDAAN DAN OLAHRAGA PROVINSI KEPULAUAN RIAU DENGAN SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING - Hendra Aris; Ngaliman Ngaliman; Bambang Satriawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes the influence of interpersonal communication, competence and work placement on job satisfaction of employees of the Riau Islands Province youth and sports department with work enthusiasm as an intervening variable. Results of Evaluation of Performance Achievements of Riau Islands Province. Based on initial observations, the results showed that 47% of the 30 respondents stated that they were dissatisfied. Meanwhile, 39% of the 30 respondents stated that they did not feel enthusiastic about working at the Youth and Sports Department of Riau Islands Province. Using primary data from 103 employees of the Riau Islands Province youth and sports department, this research found that competence had no direct significant effect on job satisfaction. In contrast, interpersonal communication and job placement were shown to have a significant influence on job satisfaction, highlighting the importance of competency to increase employee job satisfaction. Work enthusiasm has also been proven to be a significant mediator between interpersonal communication, competence and job placement on job satisfaction. The proposed recommendation is to focus on increasing employee competency and other aspects that have a more direct influence on work morale to increase job satisfaction for employees of the Riau Islands Province youth and sports department.